Evolution of adult male horn developmental phenotypes and character displacement in Xylotrupes beetles (Scarabaeidae). Issue 10 (25th March 2021) - Huang, Jen‐Pan; Morgan, Brett
Abstract: Character displacement that leads to divergent phenotypes between sympatric species has been hypothesized to facilitate coexistence and promote the accumulation of biodiversity. However, there are alternative evolutionary mechanisms that may also lead to the evolution of phenotypic divergence between sympatric species; one of the mechanisms is evolutionary contingency. We studied the evolution of the presence and absence of a major male horn phenotype, which may have ecological implications for promoting coexistence between sympatric beetles, across geographic populations from different Xylotrupes beetles. By using a previously published phylogeny with 80 Xylotrupes taxa, we estimated the transition rates between the two phenotypic states (i.e., presence vs. absence of a major male phenotype). Based on the estimated transition rates, we then simulated possible phenotypic outcomes between sympatric species. We found that sympatric species were equally likely to evolve the same versus distinct phenotypic states based on the estimated transition rates given the phylogeny. The empirically observed number of sympatric species showing different phenotypic states can be explained by evolutionary contingency alone. We discussed the importance of applying phylogenetic comparative methods when studying phenotypic evolution and more generally to investigate the effect of stochastic processes before making deterministic inferences. Abstract : Sympatric closely‐related species may exhibit different adaptive phenotypes, where character displacement is often invoked to explain such pattern. However, the evolution of distinct male horn phenotypes in sympatry can be explained by evolutionary contingency in Xylotrupes beetles. It is important to account for stochastic effect when study character evolution.